The Drosophila seminal proteome and its role in postcopulatory sexual selection - Wigby, S; Brown, NC; Allen, SE; Sepil, I (Royal Society, 2020)
Postcopulatory sexual selection, comprised of sperm competition and cryptic female choice (PCSS), has emerged as a widespread evolutionary force among polyandrous animals. There is abundant evidence that PCSS can shape the evolution of sperm. However, sperm are not the whole story: they are accompanied by seminal fluid substances that play many roles, including influencing PCSS. Foremost among seminal fluid models is Drosophila melanogaster, which displays ubiquitous polyandry, and exhibits intra-specific variation in a number of seminal fluid proteins (Sfps) that appear to modulate paternity share. Here we first consolidate current information on the evidence of similarities between many protein classes and individual proteins, including some D. melanogaster Sfp genes linked to PCSS, suggesting evolutionary conservation of broad-scale functions. We then review experimental evidence for the functions of D. melanogaster Sfps in PCSS and sexual conflict. We identify gaps in our current knowledge and areas for future research, including enhanced identification of PCSS-related Sfps, their interactions with rival sperm and with females, the role of qualitative changes in Sfps, and mechanisms of ejaculate tailoring.